Recent developments and key barriers to advanced biofuels: A short review. (June 2018) - Oh, You-Kwan; Hwang, Kyung-Ran; Kim, Changman; Kim, Jung Rae; Lee, Jin-Suk
Highlights: With 2DS, the biofuels' transport-fuel share will be 30.7% by 2060. Recent studies on advanced biofuels from different inedible feedstocks are reviewed. Important technical barriers to drop-in, algal, and electro biofuels are discussed. Biofuel deoxygenation, oleaginous algae, and electro-fermentation are emphasized. Abstract: Biofuels are regarded as one of the most viable options for reduction of CO2 emissions in the transport sector. However, conventional plant-based biofuels (e.g., biodiesel, bioethanol)'s share of total transportation-fuel consumption in 2016 was very low, about 4%, due to several major limitations including shortage of raw materials, low CO2 mitigation effect, blending wall, and poor cost competitiveness. Advanced biofuels such as drop-in, microalgal, and electro biofuels, especially from inedible biomass, are considered to be a promising solution to the problem of how to cope with the growing biofuel demand. In this paper, recent developments in oxy-free hydrocarbon conversion via catalytic deoxygenation reactions, the selection of and lipid-content enhancement of oleaginous microalgae, electrochemical biofuel conversion, and the diversification of valuable products from biomass and intermediates are reviewed. The challenges and prospects for future development of eco-friendly and economically advanced biofuel production processes also are outlined herein.